Guidance Note for the Use of Third-Party Indicators in Fund Reports. (Policy Papers; Policy Paper ;, 2018)
This note provides guidance on use of third-party indicators (TPIs) in Fund reports, in line with the policy endorsed by the Board in November 2017.